2006
DOI: 10.1073/pnas.0510136103
|View full text |Cite
|
Sign up to set email alerts
|

Early auditory experience generates long-lasting memories that may subserve vocal learning in songbirds

Abstract: In both humans and songbirds, infants learn vocalizations by imitating the sounds of adult tutors with whom they interact during an early sensitive period. Vocal learning occurs in few animal taxa; similarities in the imitation process between humans and songbirds make the songbird a unique system in which vocal learning mechanisms can be studied at the neurobiological level. One theory of vocal learning proposes that early auditory experience generates auditory memories that subsequently guide vocal imitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
224
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 211 publications
(241 citation statements)
references
References 35 publications
(73 reference statements)
15
224
1
1
Order By: Relevance
“…In particular, there were significant differences in the BOLD response amplitude for a pure tone versus CON and BOS activation, and the TUT response was different from the BOS response. We could also demonstrate that the auditory responses in the forebrain show high sensitivity to BOS [as was found in electrophysiological recordings in anesthetized birds (22,26,28,38,39)] and TUT in areas corresponding to the higher auditory area NCM [as was found in awake birds (40)], but that other stimuli activate the brain as well.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In particular, there were significant differences in the BOLD response amplitude for a pure tone versus CON and BOS activation, and the TUT response was different from the BOS response. We could also demonstrate that the auditory responses in the forebrain show high sensitivity to BOS [as was found in electrophysiological recordings in anesthetized birds (22,26,28,38,39)] and TUT in areas corresponding to the higher auditory area NCM [as was found in awake birds (40)], but that other stimuli activate the brain as well.…”
Section: Discussionsupporting
confidence: 66%
“…Indeed, unit recordings show that neuronal responses are more selectively tuned to learned vocal sounds in NCM (20,21) and CM (43)(44)(45), whereas the primary auditory subregions L2a and L2b are responsive to sounds within the wider species-specific spectrotemporal range (24,46,47). Measurement of long-term response habituation in NCM, by both electrophysiology and the study of the song stimulation-induced up-regulation of ZENK, has suggested that this area might encode the long-lasting sensory memory of the TUT (31,40). Other experiments point to the fact that NCM and CM might be involved in short-term plasticity related to song discrimination (18,19,48).…”
Section: Familiar Song Stimuli Show Selective Differential Topographymentioning
confidence: 99%
“…In adulthood, we recorded multiunit auditory responses bilaterally in forebrain NCM by using multiple microelectrodes. NCM neurons are known to respond more strongly to conspecific vocalizations than to other sounds (12,13), and show stimulus-specific adaptation: a decrease in response amplitude with repeated playback of the same sound and a slower rate of adaptation for familiar than for novel sounds (12)(13)(14). This adaptation lasts much longer for conspecific vocalizations than for other sounds and can be thought of as a long-term recognition memory for these communication signals.…”
Section: Resultsmentioning
confidence: 99%
“…We further characterized the auditory responses recorded from left and right NCM by their adaptation rate, which measures the slope of the decrease in response amplitude as a function of repetition number, and can provide a measure of the familiarity of the stimuli tested (12)(13)(14). The differences described below do not simply reflect larger initial responses because the adaptation rate measure is normalized by absolute amplitude to correct for response amplitude (Materials and Methods).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation